Caracterización De La Dinámica Del Ingreso Y Salida De Mercancías En Zonas Francas De Colombia Entre El 2012 Y 2022 (2023)
The present monograph carries out a study in which it begins from 2012 to 2022, on the free zones in Colombia that have been a key tool for the economic development and the attraction of foreign direct investment in the country. Since its creation In 1958 in the city of Barranquilla the first free zone in the country, opening in other cities like Bogotá, Buenaventura, Cartagena